Implementation of Verbal Linguistics Analysis Development in Ecolexicon and Ecoteks at Bale Sangkep, Green School Bali - Ni Putu Tirka Widanti (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
Ecolinguistics examines the whole nature of the relationship between language and the environment which is an expression of the entire reality of human life. GSB is an educational environment that preserves nature with the concept of local wisdom with a natural perspective. Lexicons derived from local, national and global languages are widely used in naming buildings, academic activities, aned daily activities. This study aims to describe the ecolexicon and ecotext found in the bale sangkep in GSB. There are 2 research focuses, first, to describe the form, meaning, and grammatical categories of the ecolexicon; second, to describe the tridimensional ecotext social praxis found in the bale sangkep in GSB. The research was conducted with a descriptive approach with qualitative methods. Data collection is done through observation, documentation, and interview methods. The data were analyzed by applying the identity method and the distributional method. The results of the study show that there are 89 lexicons related to the bale sangkep GSB. Lexicons are identified based on grammatical categories, meanings, and the existence of their environment. The total lexicons found are 69 lexicon are categorized as nouns which is consists of 19 nouns in the form of basic words, 3 nouns in the form of derivatives, 1 noun which is a compound word, and 46 other noun lexicon in the form of noun phrases. Meanwhile, the other 20 lexicons are lexicons categorized as verbs, where 1 lexicon is a basic verb and 19 lexicon is a derivative verb. The tridimensional of the ecotext are viewed from: the biological dimension, the speaker’s understanding of the physical entity of the lexicon; sociological dimension, the closeness of speakers through the use and way of implementing the lexicon entity; and ideological dimensions, collective relations, cognitive and psychological systems of speakers in the form of beliefs and beliefs about lexicon references. It can be concluded that this study reveals the richness of the lexicon in GSB as supporting data for ecolinguistics.